Pengaruh Intesitas Pemberian Tugas Mandiri Terstuktur Terhadap Hasil Belajar Mahasiswa Teknik Sipil Pada Mata Kuliah Fisika Dasar - Hidayatulloh, Alpiana; Windhari, Gusti Ayu Esty; Pangaribuan, Fika Septina (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to see how much influence structured independent assignments have on the learning outcomes of FSTT civil engineering students at the Mandalika Education University. The objects in this research were 120 students. Of the 120 students, there were those in the experimental class and there were the control classes who were chosen randomly. This research is experimental research using a quasi-experiment method. The data collection technique is by giving 7 essay questions. Student answers were analysed using descriptive qualitative methods where the data from the analysis was presented in tabular form. The results of the analysis show that the post-test results show that the experimental class has a mean value, maximum value, minimum value and standard deviation that is greater than the control class. This shows that providing structured independent assignments has an influence on student learning outcomes.